Environmental, Ecological and Food Resources in the Biodiversity Overview: Health Benefits - Alessandra Durazzo (MDPI AG, 2021)
The Special Issue “Environmental, Ecological and Food Resources in the Biodiversity Overview: Health Benefits” wants to underline the importance of classification, cataloguing and analysis of environmental, agricultural, ecological, botanical and food sources—from native species to unconventional sources and wastes—which should be promoted from the perspectives of biodiversity and sustainability [...]